“Erudite Discussion” vs. “Aimless Statement”: An Investigation into the Debate Strategies of Buddhism and Daoism in the Tang Dynasty - Xing Lan; Xi Chen (Religions, 2024)
This paper explores the argumentative strategies employed by Daoism and Buddhism in their debates during the Tang dynasty (618–907). Despite being significant in Chinese intellectual history, these debates, particularly the strategies behind them, remain understudied, and two gaps remain. First, the argumentative strategies of the two teachings are yet to be fully examined. Secondly, few studies have examined why Daoism was consistently defeated in the debates. This paper aims to address the two gaps. The paper first examines the argumentative strategies of the two teachings. Overall, the strategies employed by Buddhists were far superior to those employed by Daoists. Buddhists excelled in exposing contradictions and illogical reasoning in their opponents’ arguments. In contrast, the strategies employed by Daoists were often weak, superficial and aimless, primarily serving to undermine Buddhism, whether as a branch of Daoism or a foreign religion. The second part of the paper identifies three reasons for the disparities in argumentative strategies between the two teachings. Firstly, Buddhist doctrines and scriptures underscored the significance of debates, whereas Daoism, both from philosophical and religious perspectives, often overlooked or even discouraged their significance. Secondly, Buddhists actively learned from previous sources and debates, while Daoists displayed limited inclination to do so. Thirdly, Buddhists possessed extensive knowledge of various schools, including Daoism, while Daoists exhibited limited proficiency beyond their own tradition.